Evangelism after pluralism : the ethics of Christian witness - Stone, Bryan P., 1959- (Grand Rapids, Michigan : Baker Academic, 2018)
What does it mean to evangelize ethically in a multicultural climate? Following his successful Evangelism after Christendom, Bryan Stone addresses reasons evangelism often fails and explains how it can become distorted as a Christian practice. Stone urges us to consider a new approach, arguing for evangelism as a work of imagination and a witness to beauty rather than a crass effort to compete for converts in pluralistic contexts. He shows that the way we lead our lives as Christians is the most meaningful tool of evangelism in today's rapidly changing world. -- ‡c From publisher's description.
Competing for space in the world -- On ethics, evangelism, and proselytism -- Evangelism, empire, and rival citizenships -- The ecclesiality of salvation -- Evangelism and pluralism in the nation-state and military -- Evangelism and nonviolence -- The pluralism of consumer culture -- Evangelism and pluralistic theologies of religion -- Evangelism and beauty -- Epilogue: The meaninglessness of apologetics.
Includes bibliographical references and index.
Keywords: Missions; Evangelistic work; Cultural pluralism -- Religious aspects -- Christianity